2017
DOI: 10.1038/s41389-017-0006-6
|View full text |Cite
|
Sign up to set email alerts
|

MiR-215-5p is a tumor suppressor in colorectal cancer targeting EGFR ligand epiregulin and its transcriptional inducer HOXB9

Abstract: Growing evidence suggests that microRNAs are involved in the development and progression of colorectal cancer (CRC). In the present study, deregulation and functioning of tumor-suppressive miR-215-5p was evaluated in CRC. In total, 448 tumor tissues and 325 paired adjacent healthy tissues collected from Czech and Spain cohorts of CRC patients have been used for miR-215-5p expression analyses. A series of in vitro experiments have been performed using transient transfection of miR-215-5p mimics into four CRC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 47 publications
6
55
0
Order By: Relevance
“…As revealed by our findings, miR-215-5p substantially suppressed not just the growth but also the migration and invasion of breast cancer cells. These findings were consistent with the previous report, in which miR-215-5p inhibits the progression of colon cancer by modulating epidermal growth factor receptor ligand and Homeobox protein Hox-B9 [20]. In contrast, miR-215-5p had the potential of inhibiting the mRNA and the protein expression of Protocadherin-9 in glioma cells through regulating its promoter and 3'-UTR [21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As revealed by our findings, miR-215-5p substantially suppressed not just the growth but also the migration and invasion of breast cancer cells. These findings were consistent with the previous report, in which miR-215-5p inhibits the progression of colon cancer by modulating epidermal growth factor receptor ligand and Homeobox protein Hox-B9 [20]. In contrast, miR-215-5p had the potential of inhibiting the mRNA and the protein expression of Protocadherin-9 in glioma cells through regulating its promoter and 3'-UTR [21].…”
Section: Discussionsupporting
confidence: 93%
“…The investigation of the fundamental function of miR‐215 in the progression of malignant tumors has been carried out in preclinical research . Herein, we discovered that miR‐215‐5p was significantly downregulated in breast cancer compared with noncancerous tissue.…”
Section: Discussionmentioning
confidence: 98%
“…miRNAs are closely correlated with several tumors, including breast, gastric, ovarian, and colon cancers. [28][29][30][31] Previous investigations suggested that miR-147a plays a vital role in various cancers. 32,33 Nevertheless, the role of miR-147a in the growth and metastasis of NSCLC requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al overexpressed miR‐15 in CRC cell lines by transfection and observed an increased chemo‐sensitivity of CRC cells to oxaliplatin and 5‐Fu . The tumors that were induced by miR‐215‐5p, miR‐152, miR‐124, and miR‐506 transfected cells grow significantly slower than control group in vivo models and cancer stem cells that express hsa‐miR‐140‐5p continuously failed to form tumors . In addition, lentivirus‐miR‐490‐3p transfected CRC cells that overexpress at stable rates of miR‐490‐3p demonstrated a decreased proliferation, migration, and motility in vitro and suppressed tumor growth in vivo .…”
Section: Micrornas Prediction Of Oxaliplatin Response and Crc Treatmentioning
confidence: 99%
“…There is increasing evidence that miRNAs are a novel CRC therapeutic candidate, although their use in decreasing the growth of cancer cells is based on in vitro and in vivo studies, it is hoped that miRNAs will become a tool for than control group in vivo models [92][93][94] and cancer stem cells that express hsa-miR-140-5p continuously failed to form tumors. 95 In addition, lentivirus-miR-490-3p transfected CRC cells that overexpress at stable rates of miR-490-3p demonstrated a decreased proliferation, migration, and motility in vitro and suppressed tumor growth in vivo.…”
Section: Micrornas Prediction Of Oxaliplatin Response and Crc Trementioning
confidence: 99%